Physiological and sanitary quality of lima bean seeds treated with essential oils - Maria Geisa da Silva Soares; Hilderlande Florêncio da Silva; Edcarlos Camilo da Silva; Raví Emanoel de Melo; Luciana Cordeiro do Nascimento (Pesquisa Agropecuária Tropical)
Pathogens in lima bean seeds grown by family farmers in the Northeast region of Brazil cause great losses and can make planting areas unviable, making it essential to search for control alternatives that do not harm the environment. This study aimed to evaluate the efficiency oflemongrass, citronella, fennel, eucalyptus and basil essential oils in controlling pathogens and the seed physiological quality of traditional lima bean varieties. Two hundred seeds of the Caramelo, Raio de Sol Amarela and Raio de Sol Vermelha varieties were used per treatment. The seed physiological quality was determined based on germination, emergence and vigor tests. The following fungal genera were identified: Aspergillus, Penicillium and Fusarium. The essential oils showed antifungal effects on the pathogens, in addition to increasing the germination, emergence, shoot and root length and dry mass, as well as the emergence speed index, without interfering with seed vigor.